Permeability Study on Several Types of Dry Land Use in Aceh Besar Regency - Umar H A; Chairil Anwar; Endiyani Endiyani; Sri Agustina; Irhami Irhami; Yusran Akbar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
The variation in soil permeability levels as a result of several types of land use on dry land in Aceh Besar district is not widely known. Therefore, a study of the ability of soil to pass water (soil permeability) as a result of various land use patterns is very important to conduct research in order to maintain a sustainable environment. The metode of research used is directly survey method. The Field survey carried out by taking soil samples that were taken in a composite manner in the processing layer (0-20 cm) and intact. The variables measured include: permeability, soil organic fraction. Intact soil sampling is carried out using a ring or tube to determine soil permeability based on the constan head method. Meanwhile, composite soil samples, which are samples collected from several observation points mixed evenly into a homogeneous sample, those were used to variable soil organic fraction content using the pipette method. Permeability in the type of land use forest shrubs, mixed gardens, moor and teak forests were classified into the medium class. The order of increasing permeability starts from the type of land use for forest shrubs, mixed gardens, moorlands, teak forests and rainfed rice fields. Permeability rates didn't have correlation with organic matter content in several types of dry land use in Aceh Besar district. By increasing sand content, the pores between particles increase, the capillary action weakens, and water easily evaporates through the macro pores, or directly penetrate deep into the soil for vegetation use By increasing clay content, the effect of soil on local rainfall redistribution on vegetation growth changes from decreasing to increasing whereas sand, on the other hand, those was based on a limited distribution of soil types only with high clay content